Absence of cross‐reactivity to carbapenems in patients with delayed hypersensitivity to penicillins. Issue 12 (4th November 2013) - Romano, A.; Gaeta, F.; Valluzzi, R. L.; Alonzi, C.; Maggioletti, M.; Zaffiro, A.; Caruso, C.; Quaratino, D.
Abstract Studies performed on subjects with IgE‐mediated hypersensitivity to penicillins have demonstrated a 1% rate of cross‐reactivity between penicillins and both imipenem and meropenem, while a single study found a 5.5% rate of cross‐reactivity with imipenem/cilastatin in subjects with T‐cell‐mediated hypersensitivity to β‐lactams, mostly penicillins. We studied 204 consecutive subjects with a well‐demonstrated T‐cell‐mediated hypersensitivity to assess the cross‐reactivity with carbapenems and the tolerability of such alternative β‐lactams. All 204 subjects underwent skin tests with imipenem/cilastatin and meropenem; 130 of them were skin‐tested also with ertapenem. Subjects with negative test results were challenged with these carbapenems. All subjects displayed negative skin tests to carbapenems and tolerated challenges. These data demonstrate the absence of clinically significant T‐cell‐mediated cross‐reactivity between penicillins and carbapenems. Negative delayed‐reading skin testing with carbapenems in individuals with documented T‐cell‐mediated hypersensitivity to penicillins correlates well with subsequent clinical tolerance of therapeutic doses of carbapenems.